The mediating role of organizational commitment between calling and work engagement of nurses: A cross-sectional study - Yudi Cao; Jingying Liu; Kejia Liu; Mengyu Yang; Yanhui Liu (Elsevier, 2019)
Objective: Nurse shortage is a critical problem for global healthcare services. It impacts the quality of clinical care. Work engagement is the core competence of hospitals, which indicates employee's positive attitude toward organization and work. This study aimed to explore the relationships among calling, organizational commitment, and work engagement. Methods: A cross-sectional study was designed, and 320 nurses from tertiary hospitals in China completed the questionnaires that included demographic information, calling scale, employee engagement scale, and organizational commitment scale. Pearson correlation was performed to test the correlations among calling, organizational commitment, and work engagement. Stepwise regression analyses were performed to explore the mediating role of organizational commitment. The bootstrap method was employed to confirm the mediating effect. Results: Nurses' work engagement score was at the medium degree, whereas calling and organizational commitment were in the medium to high level. The results revealed that calling, organizational commitment, work engagement, and each dimension were positively correlated with one another (r = 0.145-0.922, P < 0.01). The organizational commitment plays a partially mediating effect between calling and work engagement (β = 0.603 to 0.333, P < 0.01). Conclusions: The mediation effect of organizational commitment was verified, which provided a comprehensive understanding of how calling impacted work engagement. Moreover, administrators should not only promote interventions to increase work engagement but also pay attention to calling and organizational commitment so as to improve their work engagement. Taken together, increased level of work engagement is required in the current nursing field. Keywords: Nurses, Calling, Employee engagement, Organizational commitment